2009
DOI: 10.1007/s11626-009-9235-0
|View full text |Cite
|
Sign up to set email alerts
|

Matrix metalloproteinase 2 activity decreases in human periodontal ligament fibroblast cultures submitted to simulated orthodontic force

Abstract: Orthodontic force compresses the periodontal ligament promoting the expression of pro-inflammatory mediators and matrix metalloproteinases responsible for tooth movement. The extent in time while periodontal cells are being treated and the increment in the amount of mechanical stress caused by the orthodontic force is thought to regulate the levels of metalloproteinases in the periodontal tissue. To study the possible regulation in the activity of metalloproteinases 2, 3, 7, 9, and 10 by simulated orthodontic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 45 publications
(73 reference statements)
0
7
0
Order By: Relevance
“…Numerous studies have shown that tensile and compressive stresses induce the expression of MMPs and TIMPs at mRNA and protein levels in PDL cells (Bolcato-Bellemin et al, 2000;Huang et al, 2008;Kook et al, 2011;Lisboa et al, 2009;Ziegler et al, 2010). The expression patterns vary under different modes of mechanical strains.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have shown that tensile and compressive stresses induce the expression of MMPs and TIMPs at mRNA and protein levels in PDL cells (Bolcato-Bellemin et al, 2000;Huang et al, 2008;Kook et al, 2011;Lisboa et al, 2009;Ziegler et al, 2010). The expression patterns vary under different modes of mechanical strains.…”
Section: Introductionmentioning
confidence: 99%
“…The role of fibroblasts is not only to secrete the components of the extracellular matrix (ECM) such as collagen, fibronectin and proteoglycan (Graham et al 2008;Spinale 2007), but also to secrete ECM-degrading enzymes called matrix metalloproteases (MMPs) (Kukacka et al 2005;Lindner et al 2012). In the case of periodontal fibroblasts, it is known that they release MMP-2, 8 and 9 (Kim et al 2012;Lisboa et al 2009;Rai et al 2010). The MMPs may degrade the collagen of the membrane, resulting in a lack of attachment cues for the cells, thereby promoting cellular detachment and eventually, cellular death.…”
Section: Discussionmentioning
confidence: 99%
“…A decrease of more than 20% on cell viability below control levels has been shown to interfere with the reliability of the data 1,11 . In our study, no significant difference was found on cell viability ratio between control and experimental groups.…”
Section: Zimography Is An Effective Methods For Detection Of Matrix Mementioning
confidence: 99%
“…The cells were stimulated with Pam 3 Cys and E. coli LPS, ligands of TLR2 and TLR4 respectively, or by centrifugation of the cultures at 141 x g for 30 min, a simulation of orthodontic force, as previously described 1 .…”
mentioning
confidence: 99%